EXPOSURE TO TOURISM CONTENT AND TOURIST VISIT INTERESTS OF INSTAGRAM FOLLOWERS @EXPLOREBANDUNG - Nabilah, Hasna; Sangun, Enisar; Damayanti, Novita (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This study aims to analyze the extent to which the frequency, duration, and attention to exposure to @explorebandung's Instagram content influence tourism visit interest. Using a quantitative approach with a survey method, this study involved 150 respondents to collect data, which was then analyzed using simple regression techniques. The findings indicate that the three aspects of tourism content exposure frequency, duration, and attention significantly influence a person's interest in visiting a tourist destination. Furthermore, the results of the coefficient of determination test reveal that 34.2% of visit interest is influenced by exposure to tourism content, while the remaining 65.8% is determined by other factors not examined in this study. These findings emphasize that social media, particularly Instagram, plays an important role in shaping tourists' decision-making processes. Thus, this study reinforces that the alternative hypothesis can be accepted, proving that exposure to social media content has a significant impact on tourists' decisions. Additionally, this research successfully achieves its objectives and provides insights into how social media can be effectively utilized as a marketing strategy in the tourism industry.